Different conjugated system Cd(II)/Hg(II) Schiff base complexes: syntheses, supramolecular metal−organic frameworks, luminescent properties and DFT study. Issue 11 (3rd June 2017) - Dong, Yu-Wei; Wang, Ping; Fan, Rui-Qing; Chen, Wei; Wang, A-Ni; Yang, Yu-Lin
Abstract: A series of different conjugated systems of 2D/3D supramolecular metal-organic frameworks (SMOFs) are constructed by C/O−H⋯Cl hydrogen bonds and π⋯π interactions. These complexes, [HgL 1 Cl2 ] (1 ), [HgL 2 Cl2 ] (2 ), [HgL 3 Cl2 ] (3 ), [CdL 4 Cl4 ]2 (4 ), and [CdL 5 Cl2 (CH3 OH)] (5 ), have been synthesized and characterized by single-crystal X–ray diffraction, 1 H NMR, FT–IR, and EA. The X-ray diffraction analyses reveal that1 features a 3D supramolecular framework with {4 4 ·6 6 } topology structure, while2, 3, and5 exhibit 3D 6-connected {4 12 ·6 3 } topology structures. Complex4 shows a two-dimensional layer with 4 4 topology structure. Based on these varied structures caused by different conjugated system, the emission maximum wavelengths of1 –5 can be tuned in a large range of 492–587 nm. Both electron-donating ability and the conjugated system in general can support λ em shift to red direction. In order to have better understanding of electronic transitions of the complexes, a time-dependent DFT study has been performed. The enhancement of the fluorescence intensities for the complexes compared to the ligands indicates potential to serve as photoactive materials. Abstract :